Home-body: A Spatial Inquiry Into Queer Material Imagination - Gallagher, Sue (Auckland University of Technology, 2020)
Home-body considers dwelling by way of topoanalysis, itself rethought through a queer materialist imagination. Utilising drawing, digital video-making and installation practice, the interrelationships between home, self and city are explored. I parallel my own dwelling with Ovid's story of Salmacis and Hermaphroditus in Book IV of the Metamorphoses, where shifting relays between bodies and environments open new, queerly-inflected spaces. The gender indeterminacy and relational union transforming Hermaphroditus in the reflective pool of Salmacis is rethought as a crucible for the transformative capacities inherent in queer and trans-corporeality more broadly. With the amphibious crossings of Salmacis’ reflective pool in mind, the research considers the transformation of Tāmaki Makaurau Auckland’s aqueous urban body. Centring this crossover is a watercolour painting produced by the design office of Gummer and Ford featuring the Dilworth Building, a neoclassical commercial building constructed between 1925 and 1927. The watercolour, dated 1926 and titled Urbis Porta, features a mirrored double to the Dilworth Building on the adjacent corner, a reflective gesture that proposed a theatrical gateway to the city. While the second building in the Urbis Porta painting was never completed, the vista offers a specific transformation in which Auckland appears as an incomplete city, one, as I argue, that opens itself to a queer phenomenological investigation. The distancing spectacle of Urbis Porta, all surface and illusionary depth, harbours another, less public orientation: my own dwelling sits within the Dilworth Building. A classically articulated ‘corner tower’ harbours this dwelling, not only registering the intersecting streets below, but also marking the now unseen crossing of the Ngā Wai o Horotiu (Horotiu Stream) and the old colonial sea-wall. The culverted stream, itself off-kilter from the city grid, resonates at a more intimate scale with the overflow of bodily matter (fallen silver hair) in interior spaces—in this case my home. The research explores the tension between these urban and bodily lines and matter through the production of what I term drawn ornamental structures. This notion is derived from Spyros Papapetros who understands ornament as extending from the decorative to the cosmological, and from José Esteban Muñoz who positions ornamentation as a key aspect of queer aesthetics. In this project ornament is taken as a transitional and excessive modality of dwelling, and in turn becomes a site for self-reflection. The creative series Urbis Porta Substitution, Line-dwelling, Urbis Porta Panoramic and Urbis Porta Itinerant explore dwelling as a network of ornamental lines and oneiric thresholds which draw out a different self-relation to dwelling. Together they renegotiate a shifting geography of gender beyond the heteronormative patterning of home and body. Pursued here are the embodied implications of dwelling. Drawing on the centrifugal and centripetal relays exhibited by bodily matter and forces, a series of installation works are produced for private and public exhibition sites.
Keywords: Spatial Design; Material imagination; Queer topoanalysis; Drawing; Installation; Dilworth Building; Dwelling; Salmacis and Hermaphroditus; Line; Home; Queer space; Trans-corporeality; Urbis Porta; Gummer and Ford; Ornamentation; Queer aesthetics